Comparison of Efficacy of Buccal Infiltration Versus Buccal and Palatal Infiltration for Maxillary First Molar Extraction (Medical Forum Monthly, 2024)
Objective: To evaluate the effectiveness of palatal and buccal infiltration against buccal infiltration only while extracting the maxillary first molar.Study Design: quasi experimental studyPlace and Duration of Study: This study was conducted at the Oral and Maxillofacial Surgery Department, Azra Naheed Dental College/Chaudhry Muhammad Akram Dental Hospital, Lahore from August 2022 to May 2023.Methods: After meeting inclusion and exclusion criteria, a total of 100 patients (50 in each of the group) were enrolled for the study. In Group A (experimental) only buccal infiltration was given for extraction of maxillary first molar while in Group B (control) buccal plus palatal infiltration was used for the extraction of maxillary first molar. Efficacy was noted in both groups. The data was entered and analyzed using SPSS version 25.Results: In our study from only buccal infiltration group the mean visual analogue score (VAS) of the patients was 2.90±1.61 and in buccal and palatal infiltration group the mean VAS of the patients was 2.64±1.67 (p-value=0.432). In only buccal infiltration group efficacy was achieved in 27(54%) patients and in buccal and palatal infiltration group it was achieved in 28(56%) patients (p-value=0.841)Conclusion: Both buccal infiltrations versus buccal and palatal infiltration are equally efficacious during extraction of maxillary first molar